2013
DOI: 10.1007/s00467-013-2543-3
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of urinary fibroblast growth factor-2 and epithelial growth factor as potential biomarkers of acute kidney injury in critically ill children

Abstract: Background Acute kidney injury (AKI) increases the morbidity of critically ill children. Thus, it is necessary to identify better renal biomarkers to follow the outcome of these patients. This prospective case–control study explored the clinical value of a urinary biomarker profile comprised of neutrophil gelatinase lipocalin (uNGAL), fibroblast growth factor-2 (uFGF-2), and epidermal growth factor (uEGF) to follow these patients. Methods Urine samples were collected from 21 healthy children, and 39 critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 57 publications
(73 reference statements)
5
23
0
Order By: Relevance
“…In the kidney, NGAL is synthesized mainly by distal tubular epithelial cells [34] and is considered to be a sensitive biomarker of AKI in critically ill children and infants [28, 3538]. However, we found that the urinary levels of NGAL did not offer early sensitivity and/or improved specificity for the identification of AKI in term newborns with HIE during the first days of life.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In the kidney, NGAL is synthesized mainly by distal tubular epithelial cells [34] and is considered to be a sensitive biomarker of AKI in critically ill children and infants [28, 3538]. However, we found that the urinary levels of NGAL did not offer early sensitivity and/or improved specificity for the identification of AKI in term newborns with HIE during the first days of life.…”
Section: Discussionmentioning
confidence: 68%
“…The SCr measurements done in control samples from healthy newborns were within the normal range. The urinary levels of neutrophil associated gelatinase lipocalin (NGAL) and epidermal growth factor (EGF) were measured using enzyme-linked-immunoabsorbent assay as described in detailed in our previous studies [26, 28]. …”
Section: Methodsmentioning
confidence: 99%
“…Another explanation may lie in the lower severity of illness in the Zappitelli cohort, as reflected by a median PRISM II score of 19 (IQR, 12) [ 28 ] for the renal failure group compared with 48.9 (IQR, 25.5 to 77.1) in our patients with AKI. Furthermore, as uNGAL and KIM-1 levels in premature infants and young children generally are higher than healthy infants and young children, the younger age of our subjects might form another explanation [ 29 , 37 , 38 ]. Last, Zappitelli and colleagues used other biomarker kits [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found a good diagnostic marker for development of AKI and persistent AKI for ≥48 hours, but not for AKI if uNGAL had been measured after a rise in SCr [ 28 ]. In later studies focused on cutoff points for AKI prediction specifically in PICU patients, researchers evaluated biomarker combinations and even suggested uNGAL as a predictor of mortality [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intense research efforts using animal models have shed light on the pathophysiology of AKI. It has been reported that the expression of Fibroblast growth factors (FGFs) and their receptors (FGFRs) are increased in the context of AKI (Wai et al, 2013;Tan et al, 2017). Furthermore, AKI is more severe upon FGFR deficiency or blockade of its signalling (Villanueva et al, 2008;Xu and Dai, 2017).…”
Section: Introductionmentioning
confidence: 99%